Singapore Airlines scoots into the low-cost long-haul category - SMIT, Willem (Institutional Knowledge at Singapore Management University, 2014)
Scoot, a new subsidiary airline of the Singapore Airlines Group (SIA), was launched in November 2011. It is a low-cost, medium to long-haul carrier that is independently operated and based out of Changi Airport in Singapore, serving value-conscious travellers in the Asia-Pacific. Throughout the region, more and more people are travelling by air for the first time as income levels continue to rise. The low-cost carrier model thrives through strong demand for cheap air travel. However, this phenomenon has led the airline industry to experience commoditisation and greater price-based competition. Full-service Singapore Airlines – with a long history and established premium brand – has a business model inappropriate for this kind of environment. Scoot was therefore established to take advantage of opportunities in the rapidly growing budget-travel segment. Campbell Wilson, a 17-year veteran of Singapore Airlines, is seconded as CEO to startup Scoot. In the year following the launch, criticisms of the new airline begin to appear. In October 2012 an editorial in a prominent publication claimed that Scoot would contaminate the Singapore Airlines brand and cannabalise sales. Wilson must address these claims.